Portrayals of the tiny house in electronic media: challenging or reproducing the Australian dream home. Issue 3 (2nd October 2018) - Penfold, Hilton; Waitt, Gordon; McGuirk, Pauline
ABSTRACT: The Australian home is embedded within social norms that align the ideal dwelling with the large detached suburban house and mass-consumption. In this paper, we present a Foucauldian discourse analysis of Australian electronic media representations of the tiny house to better understand how this dwelling type might challenge the normalisation of the Australian dream home. Our analysis suggests that the tiny house is a crucial site both for contesting and normalising sets of ideas that constitute the Australian dream home. Those advocating for tiny house living tap into narratives of 'less is more' and 'debt free living' that trouble dominant Australian housing social norms by generating material spaces that suggest affinities with affordability, slower-paced off-grid living, and enhanced sustainability. Yet, the electronic media representation of the tiny house simultaneously reproduces dominant housing social norms around luxury (even 'in nature') and a still unfettered material consumption. To conclude we draw out the broad implications of these contradictory media representations of the tiny house for Australian planners.